Measurement of the ratio of branching fractions B(B0→K∗0γ)/B(B0s→φγ ) and the direct CP asymmetry in B0→K⁎0γ - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bauer, C.; Bien, Alexander; Blouw, Johan; Britsch, Markward; Dordei, Francesca; Eisele, Franz; Färber, Christian; Fontana, Marianna; et al. (Nuclear physics. B, Particle physics, 2013)
The ratio of branching fractions of the radiative B decays B0→K⁎0γ and Bs0→ϕγ has been measured using an integrated luminosity of 1.0 fb−1 of pp collision data collected by the LHCb experiment at a centre-of-mass energy of s=7 TeV. The value obtained isB(B0→K⁎0γ)B(Bs0→ϕγ)=1.23±0.06 (stat.)±0.04 (syst.)±0.10(fs/fd), where the first uncertainty is statistical, the second is the experimental systematic uncertainty and the third is associated with the ratio of fragmentation fractions fs/fd. Using the world average value for B(B0→K⁎0γ), the branching fraction B(Bs0→ϕγ) is measured to be (3.5±0.4)×10−5. The direct CP asymmetry in B0→K⁎0γ decays has also been measured with the same data and found to beACP(B0→K⁎0γ)=(0.8±1.7 (stat.)±0.9 (syst.))%. Both measurements are the most precise to date and are in agreement with the previous experimental results and theoretical expectations.
Im Titel sind "0" und "*0" hochgestellt und "s" in B0s tiefgestellt
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, C. Bauer, A. Bien, J. Blouw, M. Britsch, F. Dordei, F. Eisele, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, F. Maciuc, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 585
Available online 24 September 2012
Gesehen am 19.03.2021